Strategi Untuk Meningkatkan Inovasi Produk Olahan Singkong Dalam Rangka Mendukung Keberlanjutan UMKM di Desa Petanang - Afri, Afri Betha; Azkananda, Fadhilah; Nurhalizah, Nurhalizah; Jaya, Frantiku; Halim, Hamid (Jurnal Nasional Pengabdian Masyarakat, 2024)
Petanang Village, located in Lembak District, Muaraenim, is known because the majority of its population relies on income from cassava-processed products. One of the superior products of Petanang Village comes from cassava processing, one of which is a typically processed class from this village, namely the typical class of Petanang Village. This study describes the innovation strategy used to develop kelasan products to increase their selling value. The research was carried out through several stages: survey, Implementation, Production, Socialization, and Marketing. By maximizing local resources in Petanang Village, Kelasan product innovation activities can be carried out with minimal capital but generate optimal profits. The results of this innovation are expected to provide a sustainable positive impact in improving the welfare of MSMEs in the area